2020
DOI: 10.1103/physrevlett.125.025102
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Ion-Scale Heating and Spectral Energy Transfer in Observations of Plasma Turbulence

Abstract: We perform a statistical study of the turbulent power spectrum at inertial and kinetic scales observed during the first perihelion encounter of the Parker Solar Probe. We find that often there is an extremely steep scaling range of the power spectrum just above the ion-kinetic scales, similar to prior observations at 1 A.U., with a power-law index of around −4. Based on our measurements, we demonstrate that either a significant (>50%) fraction of the total turbulent energy flux is dissipated in this range of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 88 publications
10
24
0
Order By: Relevance
“…We have also confirmed that the 1/4-power scaling (although not the numerical coefficient) is robust to the order of the parallel hyperdissipation (it also holds if ν 6z = 0; not shown). Spectral slopes in the ion-kinetic transition range (k ⊥ > k * ⊥ ) are seen to vary more than in the MHD range (k ⊥ < k * ⊥ ) and are very steep, α 4, in good agreement with PSP observations (Bowen et al 2020a). ⊥ above and below the break for the σ ε = 0.88 simulation of figure 5 (the averages are α ≈ 1.67 above the break and α ≈ 3.8 below the break).…”
Section: The Ion Spectral Breaksupporting
confidence: 78%
See 2 more Smart Citations
“…We have also confirmed that the 1/4-power scaling (although not the numerical coefficient) is robust to the order of the parallel hyperdissipation (it also holds if ν 6z = 0; not shown). Spectral slopes in the ion-kinetic transition range (k ⊥ > k * ⊥ ) are seen to vary more than in the MHD range (k ⊥ < k * ⊥ ) and are very steep, α 4, in good agreement with PSP observations (Bowen et al 2020a). ⊥ above and below the break for the σ ε = 0.88 simulation of figure 5 (the averages are α ≈ 1.67 above the break and α ≈ 3.8 below the break).…”
Section: The Ion Spectral Breaksupporting
confidence: 78%
“…1 At yet smaller scales, a spectral flattening (approaching the ∼k −2.8 spectrum expected for KAW turbulence (Schekochihin et al 2009;Alexandrova et al 2009Alexandrova et al , 2012Boldyrev et al 2013)) is observed due to small leakage through the barrier (see § 3.2). The behaviour matches observations of near-Sun imbalanced turbulence from PSP, which often show clear spectral breaks significantly above the ion-Larmor scale, with a non-universal spectrum between the break and a flatter spectrum at yet smaller scales (Bowen et al 2020a;Duan et al 2021). In our theory, which differs from previous phenomenologies that assume…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…width of the magnetohydrodynamic (MHD) inertial range stays approximately constant over this distance range. The steep ionscale transition range, however, is more prominent closer to the Sun, indicating stronger dissipation or an increase in the cascade rate (Bowen et al 2020), or perhaps a build-up of energy at these scales (Meyrand et al 2020). The overall increase in the turbulence energy flux, compared to the bulk solar wind kinetic energy flux, was found by Chen et al (2020) to be consistent with the reflection-driven turbulence solar wind model of Chandran et al (2011), showing that this remains a viable mechanism to explain the acceleration of the open field wind.…”
Section: Introductionmentioning
confidence: 99%
“…At ion kinetic scales magnetic spectra steepen, due to some combination of dispersive and dissipative effects, leading to a sub‐ion scale energy cascade (Alexandrova et al., 2008, 2009, 2012; Sahraoui et al., 2009, 2010). Kinetic spectra with approximate k −2.7 scaling characterize the solar wind at 1 AU and the inner heliosphere (Alexandrova et al., 2012; Bowen, Mallet, Bale, et al., 2020; Chen et al., 2010; Sahraoui et al., 2009, 2013). The observed steepening is consistent with the dispersion of Alfvénic to kinetic Alfvén wave (KAW) turbulence alongside some intermittency or dissipation (Boldyrev & Perez, 2012; Chen et al., 2013; Franci et al., 2015, 2016; Howes et al., 2011; Schekochihin et al., 2009).…”
Section: Introductionmentioning
confidence: 99%